Nâng cao thành quả an toàn thông tin: Vai trò của hành vi né tránh nguy cơ và sự sẵn sàng của doanh nghiệp - Nguyễn Hữu , Bình; Phạm Trà , Lam; Nguyễn Phước Bảo , Ấn; Nguyễn Quốc , Trung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
Information security (ISe) threats are increasing and seriously impacting sustainable business operations. Due to the lack of studies on ISe performance from a human resource management perspective, this study tested a model to explain how ISe performance is affected by ISe readiness, threat avoidance behavior, and other antecedents. The PLS analysis of 320 enterprises showed that ISe readiness fully mediated the impact of threat avoidance behavior on ISe performance. The authors also confirmed the significant roles of risk avoidance motivation, ISe education, training, awareness programs, and social influence on threat avoidance behavior and ISe readiness. These findings provide business managers, ISe consulting firms, and authorities with insights into strategies to enhance ISe performance.
Keywords: Information security performance; Information security readiness; Threat avoidance behavior; Vietnam